Screening for Fragile X Syndrome Among Filipino Children with Autism Spectrum Disorder - Dy, Angel Belle C.; Tanchanco, Lourdes Bernadette S.; Sy, Jenica Clarisse Y.; Levantino, Myla Dominicina; Hagerman, Randi J. (Journal of autism and developmental disorders, 2023)
Individuals with autism spectrum disorder present with difficulties in social communication, restricted interests or behaviors and other co-morbidities. About 2 to 10% of cases of autism have a genetic cause, and Fragile X Syndrome (FXS) is reported in 0 to 6.5% of individuals with autism. However, the FXS and premutation prevalence among Filipino children has never been reported. The aim of the study was to establish the presence of FXS or premutation carriers among Filipino children with autism and to describe the phenotypic characteristic of cases identified. Blood was collected from 235 children aged 2–6 years old and diagnosed with autism. Samples were analyzed using PCR methods to amplify CGG repeats in the FMRI gene. The diagnosis of autism was confirmed through the Autism Diagnostic Observation Schedule-2. Additional characteristics were documented from a physical examination, Griffiths Scales of Child Development assessment and a parent-answered questionnaire using the Vineland Adaptive Behavior Scale. Fragile X testing through PCR methods in 235 children with diagnosed autism showed 220 (93.6%) were negative, no full mutations, 1 (0.436%) premutation carrier and 14 (5.95%) cases contained intermediate alleles. The FXS testing was limited to confirmed cases of autism, which is considered a high-risk group and does not provide prevalence for the general Filipino population. Subjects were self-referred or referred by clinicians, which may not represent the Filipino autism population with a bias towards those with means for clinical consultations and ability to travel to the place of testing. Samples were not measured for mosaicism, DNA methylation or AGG interspersion patterns. These may have effects on the CGG repeat expansion and overall presentation of FXS. Findings from a single premutation carrier cannot characterize features distinctly present in Filipinos with the mutation. Nevertheless, these results support the data that the prevalence of FXS in Asian populations may be lower than non-Asian populations. This can contribute to a better understanding of FXS and genetic causes of autism in the Philippines and other Asian populations.